GEOPHYSICAL INVESTIGATION OF ARCTIC ICE PACK. - Kutschale,H. W.; Farrand,W. R. (1963)
Experiments were made on shallow-water sound propagation on the Arctic continental shelf. The waves were successfully interpreted in terms of normal-mode theory for an ice-water-sediment acoustic system. Current measurements made on Station Alpha in the central Arctic Ocean show a clockwise spiral which is not as pronounced as the Ekman spiral for homogeneous water. (Author)